Antiviral Efficacy of Tinospora cordifolia – A Review (Asian Journal of Pharmaceutics (AJP), 2024)
Since ages, plants have had a pivotal role as medicine due to their therapeutic value. Tinospora cordifolia is awell-known plant with versatile medicinal properties including hypoglycemic, anti-inflammatory, antioxidant,immunomodulatory, and antimicrobial, which can be attributed to its secondary metabolites. Viral infectionsconstitute a major faction of human diseases. Developing efficient and novel therapeutic agents to combat viraldiseases is an ongoing process, wherein plant-derived natural products are a potential source. T. cordifolia hasbeen explored for its use in viral infections as an immunomodulatory and antiviral agent. Bioactive components ofthe plant, such as berberine, tinosponone, tinocordiside, isocolumbin, magnoflorine, tinosporin, and cordiofolisidehave been reported to exhibit antiviral efficacy. The present review summarizes the efficacy of T. cordifolia as ananti-viral agent and its role in combating viral infections.